2015
DOI: 10.1111/ans.13397
|View full text |Cite
|
Sign up to set email alerts
|

Patient‐related factors influence the risk of developing intestinal stoma complications in early post‐operative period

Abstract: Patient-related risk factors influence the risk of developing a stoma complication more than surgery-related risk factors. Preoperative and post-operative interventions, planning, vigilance and management should be focussed to at-risk groups, particularly obese patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
32
0
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 29 publications
3
32
0
6
Order By: Relevance
“…Stoma complications include poor siting, parastomal hernia, prolapse, retraction, ischemia/necrosis, peristomal dermatologic problems, mucocutaneous separation, and pyoderma gangrenosum; the reported incidence rate is 10–70% [1] , [2] , [3] . Stomal retraction is defined as a stoma that is 5 mm or more below the skin surface, and the reported incidence rate is 1.4–24% [1] , [2] , [5] , [6] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Stoma complications include poor siting, parastomal hernia, prolapse, retraction, ischemia/necrosis, peristomal dermatologic problems, mucocutaneous separation, and pyoderma gangrenosum; the reported incidence rate is 10–70% [1] , [2] , [3] . Stomal retraction is defined as a stoma that is 5 mm or more below the skin surface, and the reported incidence rate is 1.4–24% [1] , [2] , [5] , [6] .…”
Section: Discussionmentioning
confidence: 99%
“…Stomal retraction and excrescent skin folds result in poor fitting, frequent leakage, and peristomal dermatologic problems [4] , [7] , [8] . Stomal retraction is caused by the thick subcutaneous fat and abnormal skin folds in obese patients, as well as by the excess tension that is the result of inadequate mobilization [2] , [3] , [4] , [7] . Although the rectus sling method of colostomy with double orifices was reported to be a preventive approach, our case had a colostomy with a single orifice so we were unable to utilize this method [9] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the nurse should contact with the patient who will undergo stoma surgery as early as possible. This contact, preferably in the preoperative phase, promotes the establishment of an interpersonal relationship between the nurse and the person-family and the development of trust and respect to bolster the learning process (Pantaroto, 2015), as well as influence the process of recovery in the postoperative phase, the prevention of complications, and the adaptation to life with a stoma (Harilingam et al, 2015;Goldblatt et al, 2017;Repic & Ivanovic, 2017;Zeigler & Min, 2017). It is important to identify the patients' level of stoma self-care competence in the preoperative phase so that nurses can better identify their needs and prescribe nursing interventions for meeting them.…”
Section: Introductionmentioning
confidence: 99%
“…Complications of ileostomy, including abscess, stenosis, allergy, edema, irritative or mechanical trauma, hemorrhage, dermatitis, necrosis, folliculitis, parastomal herniation, prolapse, retraction, and parastomal varices, can occur soon after or many years after the procedure. 3 According to Leong et al, the incidence of stomal complications reported in a 20-year follow-up of CD patients was about 59%; the most common complications were skin problems (34%), intestinal obstruction (23%), retraction (17%), and parastomal herniation of the oblique muscles (16%). 4 …”
Section: Introductionmentioning
confidence: 99%